2020
DOI: 10.36469/jheor.2020.13607
|View full text |Cite
|
Sign up to set email alerts
|

Zia A, Brassart A, Thomas S, et al. Patient-Centric Structural Determinants of Adherence Rates Among Asthma Populations: Exploring the Potential of Patient Activation and Encouragement Tool TRUSTR to Improve Adherence

Abstract: Background: Lack of adherence with prescribed medications among the asthma populations exacerbates health outcomes and increases social and economic costs. Objectives: The proposed study aims to model patient-centric structural determinants of adherence rates among asthma patients and explore the potential of mobile health apps such as the TRUSTR platform to improve adherence using its power of monetary and non-monetary chatbotting and non-monetary nudges. Following specific hypotheses are tested: (1) Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Nudge‐based interventions influence behavior without limiting an individual's freedom of choice. Existing examples in the management of chronic diseases such as diabetes mellitus and asthma include use of short message service (SMS) reminders, monetary and non‐monetary rewards, mobile application‐based interventions, and low‐technology reminders to place in the home 19,20 . In the context of AR, Wang et al demonstrated the value of daily SMS in increasing self‐reported adherence to INCS and clinic attendance; patients in the SMS group were less likely to forget to use their AR medications 8 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nudge‐based interventions influence behavior without limiting an individual's freedom of choice. Existing examples in the management of chronic diseases such as diabetes mellitus and asthma include use of short message service (SMS) reminders, monetary and non‐monetary rewards, mobile application‐based interventions, and low‐technology reminders to place in the home 19,20 . In the context of AR, Wang et al demonstrated the value of daily SMS in increasing self‐reported adherence to INCS and clinic attendance; patients in the SMS group were less likely to forget to use their AR medications 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Existing examples in the management of chronic diseases such as diabetes mellitus and asthma include use of short message service (SMS) reminders, monetary and non‐monetary rewards, mobile application‐based interventions, and low‐technology reminders to place in the home. 19 , 20 In the context of AR, Wang et al demonstrated the value of daily SMS in increasing self‐reported adherence to INCS and clinic attendance; patients in the SMS group were less likely to forget to use their AR medications. 8 Such interventions should be employed in the treatment of AR to improve adherence to treatment given the high prevalence of the disease and potential for development or worsening of asthma and chronic rhinosinusitis.…”
Section: Discussionmentioning
confidence: 99%